Morfologia e sedimentação da praia de Marudá (Marapanim/PA) e a segurança ao banho - ANTUNES, Allyson Gabriel Franco (2022)
The beaches are characterized and highlighted by their high dynamism and their role of coastal protection against oceanographic processes, it is also an area of diverse use for the population, as well as a habitat area for marine animal and plant species. Marudá beach, located on the Atlantic Coast of the State of Pará, presents this high dynamism and population diversity, highlighting an urban growth, added to the considerable increase in tourism during summer seasons. This population is subject to the risks of erosion that occurs in the place, and also to aquatic accidents, due to the lack of knowledge of the beach's morphology and hydrodynamics. In this sense, the presupposed work is justified in providing important information in taking mitigating measures for the aforementioned problems, and assisting the understanding of bathers in relation to the main oceanographic risks to which they are subject. Thus, the analysis of sedimentation, the coastal morphology of Marudá beach and the clarification on the safety of bathing on the beach was the main objective of this work. To achieve this, sampling of topographic and sedimentological data was carried out during the month of October 2019 (Amazonian dry season), and interactions with bathers through conversations and application of questionnaires. The Birkmeier method (1985) was used as a reference for the topographic survey, using as material, the Total Station equipment and a stick with a reflective prism, which allow faster measurements and accuracy of the results. In addition, sediment was collected in the three different profiles of topographic measurements, for later analysis in the laboratory. With the use of wave height data measured in the field using a gradable ruler, and by identifying the beach morphodynamic state, it was possible to calculate the scale of dangerousness to the bath. These results were associated with the data obtained from questionnaires applied in situ with bathers, as well as the information acquired from dialogues with the population during the distribution of biodegradable pamphlets in which they contained diverse information on prevention of some risks commonly identified on the beaches . All these data helped in the knowledge about the dangers with the improper use of the beaches, the problems involving drowning and other accidents, guiding, thus, for safe bathing on beaches. It was identified that in the dry period, the Marudá beach was classified as a morphodynamic state of Bank and Longitudinal Cavas, with a moderate degree of dangerousness (4-6), with the breaking of the waves being the main associated danger, in addition to hazards such as: objects sharp, aquatic animals and the preference for bathing in a wave break zone. As it is a beach with many benches and pits, more than one wave break zone originates on the beach, increasing the danger with both the waves and the currents generated by them. Sedimentology, typical of beaches with strong tidal influence, was predominantly fine sand, due to the high level of transport and rework of sediments that the beach is subject to, as it is located in a fluvial-marine area, that is, with dynamism governed by the estuary Marapanim and the Atlantic Ocean. It is concluded that the data obtained are of paramount importance for the extensive knowledge of the estuarine and Amazonian marine region, and for the safety of bathers, especially those who frequent beaches with these characteristics, where in summer season there is an even greater demand.